Eksploitasi Tubuh Perempuan Dalam Perfilman Horor Indonesia Studi Politik Tubuh Terhadap Film Suster Keramas - Silitonga, Natasha Abeline; Erviantono, Tedi; Puspitasari, Ni Wayan Radita Novi (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to examine how the objectification of women and the exploitation of women's bodies are depicted in the movie "Suster Keramas".The author utilizes theories of patriarchy, women's objectification, and capitalism to analyze this topic.The author finds that the movie "Suster Keramas" overtly employs the objectification of women, evident through sensual scenes and the use of Rin Sakuragi, as the main character. The film's producers employ such tactics to attract audiences and generate profit. Despite the negative responses, "Suster Keramas" managed to attract a significant audience of 800,000 viewers at that time. This indicates that the film perpetuates patriarchal discourse through the objectification of women within its narrative. Moreover, the profit motive within the film aligns with the exploitative and expansionist nature of capitalism, thereby justifying the exploitation of women's bodies as a means to maximize profits. Hence, patriarchy and capitalism are closely intertwined in the movie "Suster Keramas."